2014
DOI: 10.1136/bjsports-2014-093493
|View full text |Cite
|
Sign up to set email alerts
|

Reality check: the cost–effectiveness of removing body checking from youth ice hockey

Abstract: Our study suggests that a policy disallowing body checking in Pee Wee ice hockey is cost-saving (associated with fewer injuries and lower costs) compared to a policy allowing body checking. As we did not account for long-term outcomes, our results underestimate the economic impact of these injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…This is an underestimate of avoided costs, given the additional youth soccer participation in schools and recreational contexts where registration with Canadian Soccer Association is not required. In a similar cost-effectiveness analysis in youth ice hockey in Alberta, evaluating the cost avoidance in delaying body checking from age 11 to age 13 it was projected that 1273 injuries would be avoided in 11 and 12 year old hockey players annually and $213 280 in healthcare costs would be avoided 26. In both studies, an assumption is made that the IRs and resource use patterns of players in rural Alberta would not differ from those playing in the city.…”
Section: Discussionmentioning
confidence: 99%
“…This is an underestimate of avoided costs, given the additional youth soccer participation in schools and recreational contexts where registration with Canadian Soccer Association is not required. In a similar cost-effectiveness analysis in youth ice hockey in Alberta, evaluating the cost avoidance in delaying body checking from age 11 to age 13 it was projected that 1273 injuries would be avoided in 11 and 12 year old hockey players annually and $213 280 in healthcare costs would be avoided 26. In both studies, an assumption is made that the IRs and resource use patterns of players in rural Alberta would not differ from those playing in the city.…”
Section: Discussionmentioning
confidence: 99%
“…This is important given the significant clinical, economic,22 academic and psychosocial consequences of youth hockey injuries. Research on Peewee, Bantam and Junior Gold hockey players showed FP effectiveness in reducing penalties and injury rates, thereby supporting the results of this study 11…”
Section: Discussionmentioning
confidence: 99%
“…Selective measures address subgroups of sports participants distinguished by age, sex, experience, or other sociodemiographic or sports-related risk indicators, but who, on individual examination, do not exhibit explicit individual risk factors. Examples of selective measures are knee injury prevention programs for female adolescent football players [4], charging bans in youth ice hockey [15], and use of visors throughout junior ages in bandy (a team ball sport played skating with sticks) [16]. Indicated measures are delivered to individuals presenting an indicator that identifies the specific individual as being at higher than average risk for the future development of an injury or disease.…”
Section: Classification Of Prevention Based On Risk Factorsmentioning
confidence: 99%